2022
DOI: 10.1021/acsomega.1c06681
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Serum Proteomics by DIA-MS with In Silico Spectral Libraries Reveals Dynamics during the Active Phase of Systemic Juvenile Idiopathic Arthritis

Abstract: In serum proteomics using mass spectrometry, the number of detectable proteins is reduced due to high-abundance proteins, such as albumin. However, recently developed data-independent acquisition mass spectrometry (DIA-MS) proteomics technology has made it possible to remarkably improve the number of proteins in a serum analysis by removing high-abundance proteins. Using this technology, we analyzed sera from patients with systemic juvenile idiopathic arthritis (sJIA), a rare pediatric disease. As a result, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
(119 reference statements)
1
6
0
Order By: Relevance
“…In accordance with these data, a recent study has also suggested profiling the activity of PBMC's immunoproteasome as a sensitive biomarker for the disease activity of Systemic juvenile idiopathic arthritis (sJIA), enabling the detailed evaluation of response to treatment. This study also demonstrated that proteasome subunits expression, as measured by mass-spectrometry analysis, immediately increased upon inflammatory activation in sJIA [78].…”
Section: Standard-and Immunoproteasome Activity Profiles In Health An...supporting
confidence: 63%
“…In accordance with these data, a recent study has also suggested profiling the activity of PBMC's immunoproteasome as a sensitive biomarker for the disease activity of Systemic juvenile idiopathic arthritis (sJIA), enabling the detailed evaluation of response to treatment. This study also demonstrated that proteasome subunits expression, as measured by mass-spectrometry analysis, immediately increased upon inflammatory activation in sJIA [78].…”
Section: Standard-and Immunoproteasome Activity Profiles In Health An...supporting
confidence: 63%
“…Throughput is important in large cohort studies and in major diseases with large numbers of patients, but for diseases with low morbidity, it is difficult to collect many samples; therefore, a deep analysis is considered more suitable than throughput. We often study rare and intractable diseases in children (23)(24)(25)(26), and it is not possible to actually collect a large number of specimens; therefore, a deeper analysis is required. Depending on the purpose and target disease, the combination of the LEL method and the ultra-deep proteome analysis system will be a useful method for biomarker discovery.…”
Section: Ultra-deep Proteome Analysis For Plasma and Serummentioning
confidence: 99%
“…Advances in mass spectrometry (MS) and proteome analysis technologies have revealed that body fluids not only contain locally expressed proteins but also many disease-related proteins secreted and shed from distant pathological tissues. , The collection of body fluids is less costly and less invasive to subjects. Considering these advantages, body fluid proteome analysis has attracted attention as a useful approach for clinical and pharmacological studies. …”
Section: Introductionmentioning
confidence: 99%